Suggestive Potential of Language Units in Advertising Texts of International Women’s Glossy Fashion Magazines - O. A. Selemeneva (Научный диалог, 2019)
We study the language means of logically unreasoned speech impact on the recipient in advertising texts. The relevance of the issue of speech exposure for modern philology is due to technological progress, changing formats of exhortatory communication, research interest in a number of problems of linguistic pragmatics, as well as the formation of a relatively young direction in Russian science - suggestive linguistics. The empirical material of the study is international women's glossy fashion magazines, which are in demand in the domestic media market: “Vogue”, “ELLE”, “Harper’s Bazaar”, “Marie Claire”, “Glamor”, “InStyle”, “Cosmopolitan”. It is shown that a hidden effect on the female target audience with the aim of encouraging buying is provided by a combination of linguistic units of word-formation, lexical, morphological and syntactic levels: some prefix morphemes, certain groups of onyms, terminological vocabulary, abstract nouns and nouns with a “wide-valued” meaning, evaluative adjectives, imperative verbs, personal and possessive pronouns, quantitative-nominal phrases, emotional and interrogative sentences. The distinguished linguistic units explicate certain communicative strategies, create various psychological effects, activate prevailing stereotypes and replace logical argumentation with positive associations.